Sacha Inchi (Plukenetia volubilis): Potential Bioactivity, Extraction Methods, and Microencapsulation Techniques - Sarah Gustia Redjeki; Alfa Fildzah Hulwana; Rizqa Nurul Aulia; Ira Maya; Anis Yohana Chaerunisaa; Sriwidodo Sriwidodo (Molecules)
Sacha inchi (Plukenetia volubilis L.), an oilseed native to the Peruvian rainforest, has garnered attention for its valuable components and its potential applications in the food, pharmaceutical, and nutraceutical industries. Sacha inchi oil is rich in fatty acids, particularly omega-3, omega-6, and omega-9, along with antioxidants such as tocopherols, which collectively contribute to cardiovascular health, antioxidant, anti-inflammatory, antiproliferative, and neuroprotective effects. The susceptibility of the oil to oxidation poses significant challenges for both storage and processing, making it essential to employ microencapsulation technologies to preserve its integrity and extend shelf life. This paper aims to provide a review of the therapeutic potential, extraction methods, and microencapsulation strategies for enhancing the oil’s stability and bioavailability. Optimizing both extraction processes and encapsulation strategies would enhance the oil’s stability and bioavailability, enabling it to be more effectively utilized in functional foods and therapeutic applications across the nutraceutical and pharmaceutical fields.